The Implementation of the Peer Tutor Method in the Learning Process of Islamic Religious Education to Increase Learning Motivation - Saadah, Miftahus; Ehwanudin, Ehwanudin; Wijaya, Adi (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2025)
This research aims to increase student learning motivation through the application of the peer tutoring method and to describe the extent to which this improvement occurs. This research is included in the type of classroom action research, which involved 32 students in class VIII-A from a junior high school located on Jl. Bison, 28 Purwosari Metro Utara Kota Metro as research subject. In the data collection process, researchers used two techniques, namely observation and questionnaires. The research results show that the application of the peer tutoring method has proven effective in increasing students' learning motivation, especially in Mathematics subjects with a focus on multiplication and division of fractions. The increase in student learning motivation is reflected in the data obtained, where students' initial motivation before implementing the action only reached 31% in the pre-cycle. After implementing the first cycle, student learning motivation increased significantly to 65%, and in the second cycle, student motivation reached 87%. Based on these results, it can be concluded that the level of student learning motivation is in the very good category. Therefore, it can be stated that the implementation of this research action was successful in achieving the stated objectives. The application of the peer tutoring method is not only effective in increasing understanding of the material, but also successful in encouraging students to be more motivated in learning.